2006
DOI: 10.1590/s0034-72992006000100016
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia e segurança de Sultamicilina (Ampicilina/Sulbactam) e Amoxacilina/Clavulanato no tratamento das infecções de via aéreas superiores em adultos: um estudo multicêntrico, aberto e randomizado

Abstract: As IVAS em crianças e adultos são os motivos mais freqüentes de consulta médica e os que mais demandam o uso de antibióticos. A crescente resistência bacteriana causada pela produção das beta-lactamases constitui um dos mais sérios problemas atuais. A Sultamicilina é uma pró-droga dupla da ampicilina e do sulbactam, um potente inibidor de beta-lactamases que pode fazer frente a estas dificuldades. OBJETIVO: avaliar a eficácia, segurança e tolerabilidade da Ampicilina/Sulbactan comparada à Amoxacilina/Ácido Cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The ampicillin-sulbactam association has been considered a potent inhibitor of beta-lactamases, which can inactivate this resistance (FERREIRA et al, 2006). In this study, 40% of the isolates showed intermediate resistance profile to these antimicrobials.…”
Section: Target Genes and Primers Utilizedmentioning
confidence: 72%
See 1 more Smart Citation
“…The ampicillin-sulbactam association has been considered a potent inhibitor of beta-lactamases, which can inactivate this resistance (FERREIRA et al, 2006). In this study, 40% of the isolates showed intermediate resistance profile to these antimicrobials.…”
Section: Target Genes and Primers Utilizedmentioning
confidence: 72%
“…Some authors have associated beta-lactamase production with an increase in antimicrobial resistance (FERREIRA et al, 2006). The selective pressure exerted by antimicrobials such as beta-lactams compounds is related to the selection of resistant strains including extended spectrum beta-lactamase producing enterobacteria (ESBL) (CHOI et al, 2008).…”
Section: Target Genes and Primers Utilizedmentioning
confidence: 99%